(untitled) (Medico Legal Update, 2020)
Classification of Cancer Model Clinically Actionable Genetic Mutations Using Machine Learning Algorithms. Its task is to classify genes based on text evidence from clinical issues with good results. If a normal person has symptoms of cancer we can find it easily, but we have nine types of viruses in cancer in that which type of viruses has been attacked to the person cannot be easily predict by the doctors. So in hospitals there will be a clinical pathologist. Clinical pathologist has the data’s of cancer attacked before and he will collect the gene sample and the person blood sample and predict which type of virus of cancer will attack to the person.